Becoming a Global Leader : Examining the Barriers for Chippewa Valley Business - Becker, Eric (My University, 2010)
International trade supports 6.8% of Wisconsin?s private sector employment and has become increasingly important as the demand for products from the domestic market decreases. Technology and trade agreements have removed many barriers to the international arena; however companies still face significant obstacles when conducting international business. According to the 2008 ?Wisconsin Next Generation Manufacturing? study, 60 percent of the 500 surveyed manufacturers said they were making ?little or no progress? toward becoming a world-class global player. Research has proven that a majority of exporters are small and medium-sized enterprises (SMEs) (i.e., businesses with 500 or less employees). The objective of this study is to examine the barriers to internationalization experienced by small and medium-sized enterprises that export their product from the Chippewa Valley region of Northwestern Wisconsin.
Color poster with text and diagrams.
Keywords: Chippewa River Valley (Wis.)--Commerce; Exports--Wisconsin--Chippewa River Valley; Export marketing--Wisconsin--Chippewa River Valley; Export marketing--Social aspects; Posters